(untitled) (Research, Society and Development, 2020)
This article aims to analyze and reflect the teaching and learning process in the area of Mathematical Education and present an educational product, aimed at high school, as a methodological innovation. The educational product developed was the CBN Diagram, which can be understood as a diagram of conversions between numerical bases. The research was justified, since the textbooks, commonly used for teaching conversions, offer various techniques considered complex by students recently arrived in integrated technical high school. The research was developed at the Federal Institute of Minas Gerais, in two different classes on one of the institution’s campuses, in which the CBN Diagram was used only in one of them for a comparative study. The methodological choice was based on the participant observation technique. The motivation of the proposal is based on the questioning of traditional teaching practices in relation to mathematical education. The results indicate the achievement of significant learning, by Ausubel, when the diagram is applied together with the theory of conversions between the bases of numerical systems, improving students’ academic performance.